Pendampingan Pembentukan Bank Sampah Di Aisyiyah Ranting Desa Mendak, Kecamatan Delanggu, Kabupaten Klaten - Esri Rusminingsih; Ambar Winarti; Chairil Hana Mustofa; Marwanti Marwanti; Romadhan Tri Purnomo; Supardi Supardi (Universitas Muhammadiyah Klaten, 2024)
The issue of waste is still a major problem in Indonesia. Waste has a negative impact on the environment and public health. The new paradigm of waste management is to consider waste as having economic value, and can be used as energy, compost, fertilizer, and raw materials for industry. The partner's problem is the lack of public knowledge in waste management, the low level of public awareness in managing waste wisely. The purpose of this community service is to provide assistance in the formation of a waste bank in Aisiyah Ranting Mendak, Kec. Delanggu, Kab. Klaten. This activity is in partnership with Aisiyah ranting Mendak village with a total of 50 housewives. The activity was carried out in 3 stages, namely 1) counseling about waste banks, 2) waste collection, and 3) financial management of waste banks. This community service activity contributed to increasing respondents' knowledge about waste management, forming a waste bank management structure (chairman, secretary, treasurer, and mobilizing members), and increasing the income of waste bank customers. Customer money is used for health screening every 3 months (cholesterol, blood glucose and uric acid checks), as well as member savings and loans. The community environment is cleaner and waste has economic value. Waste bank Aisiyah ranting Mendak increases economic value and keeps the environment clean in the community of Mendak village, Delanggu District, Klaten Regency.